Is cardiac arrest an inflammatory state? Adding steroid into ACLS guidelines will save more lives? - Chowdhury, Tapati; Nath, Arpona Dev; Islam, Tasbirul (Bangladesh Critical Care Journal, 2018)
Cardiac arrest is a life-threatening condition with low survival rate. Over the years ACLS guidelines have been developed to reduce cardiac arrest specific mortality rate. In this review article, the authors researched steroid use during and after CPR for determining its effect on survival rate and post cardiac arrest disabilities. Scholarly articles from well-known reputed journals relevant to both cardiac arrest and steroid use since 1960 have been reviewed. This article first examines the question whether cardiac arrest can be considered an inflammatory state. Afterwards, evidence of the beneficial role of steroid use in cardiac arrest and in other cardiac conditions have been outlined. In conclusion, this review paper summarizes any benefits of steroid use in cardiac arrest. Bangladesh Crit Care J September 2018; 6(2): 92-94